Determining the Company Marketing Sales Perfomance Using the Operational Competitiveness Rating Analysis (OCRA) Method - Ismawati; Pandu Adi Cakranegara; Amin Budiastuti; Kurniawansyah; Tienni Mariana Simanjorang (Enrichment : Journal of Management, 2022)
Sales marketing can assist improved sales for a firm and can undoubtedly play a significant role in the process of introducing a new product. One of the initiatives in human resource management to build and enhance employee capabilities, particularly sales marketing in support of increasing sales, which is one of the company's goals, is sales marketing performance appraisal. Company executives typically assess each marketing salesperson's sales turnover when deciding which among them is the finest marketing salesperson. The goal of this study is to apply an operational competitiveness rating analysis method (OCRA) marketing performance assessment model with the assessment criteria namely discipline (C1), softskill and hardskill (C2), quality of work (C3), and absenteeism (C4) in order to avoid mistakes in decision-making or to give the impression of subjectivity in determining the best salesman. The study's findings, specifically the calculation of the final value of the ranking, led to an analysis showing how heavily the final result of the preference value for each alternative is influenced by using the maximum and minimum values for the performance rating of the alternatives in extraction.